Cloning and Characterization of Two Pyruvate Decarboxylase Genes from Pichia stipitis CBS 6054 - Lu, Ping (American Society for Microbiology, 1998)
In Pichia stipitis, fermentative and pyruvate decarboxylase (PDC) activities increase with diminished oxygen rather than in response to fermentable sugars. To better characterize PDC expression and regulation, two genes for PDC (PsPDC1 and PsPDC2) were cloned and sequenced from P. stipitis CBS 6054. Aside from Saccharomyces cerevisiae, from which three PDC genes have been characterized, P. stipitis is the only organism from which multiple genes for PDC have been identified and characterized. PsPDC1 and PsPDC2 have diverged almost as far from one another as they have from the next most closely related known yeast gene. PsPDC1 contains an open reading frame of 1,791 nucleotides encoding 597 amino acids. PsPDC2 contains a reading frame of 1,710 nucleotides encoding 570 amino acids. An 81-nucleotide segment in the middle of the β domain of PsPDC1 codes for a unique segment of 27 amino acids, which may play a role in allosteric regulation. The 5′ regions of both P. stipitis genes include two putative TATA elements that make them similar to the PDC genes from S. cerevisiae, Kluyveromyces marxianus, and Hanseniaspora uvarum.